2015
DOI: 10.1002/cplx.21645
|View full text |Cite
|
Sign up to set email alerts
|

On using compressibility to detect when slime mould completed computation

Abstract: Disclaimer UWE has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material. UWE makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.UWE makes no representation that the use of the materials will not infringe any patent, copyright, trademark or other property or proprietary rights. UWE accepts no liability fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…[11][12][13] For example, the adaptive 'learning' behavior of slime mould Physarum polycephalum (PPM) was described in terms of memristor model; 14,15 the mould also resulted to be able to perform complex tasks of the information processing. [16][17][18] Gale et al 19 observed occasionally that PPM protoplasmic tubes showed hysteretic current-voltage characteristics, consistent with those of the memristive systems.…”
Section: Introductionmentioning
confidence: 85%
“…[11][12][13] For example, the adaptive 'learning' behavior of slime mould Physarum polycephalum (PPM) was described in terms of memristor model; 14,15 the mould also resulted to be able to perform complex tasks of the information processing. [16][17][18] Gale et al 19 observed occasionally that PPM protoplasmic tubes showed hysteretic current-voltage characteristics, consistent with those of the memristive systems.…”
Section: Introductionmentioning
confidence: 85%
“…where a denotes the free flow travel time given here. The original parameter b can be expressed as: b = B · α c P ower (28) where α and c denote the free flow traffic time and the capacity flow, respectively. P ower is set as 4 and assume the traditional BPR value of B = 0.15, so we can get the same travel time equation as Eq.…”
Section: Examplementioning
confidence: 99%
“…Recently, the slime mould Physarum polycephalum becomes a popular living computing substrate [26,27]. Physarum machines are proved to be the most successful biological substrates in solving problems of computation geometry, optimization, and logic because they are easy to realize [28]. In this article, a modified Physarum-inspired model is proposed to solve the UE traffic assignment problem.…”
Section: Introductionmentioning
confidence: 99%
“…A number of foraging models have been proposed [24][25][26][27][28][29]. Related researches illustrate that Physarum has an ability to solve maze navigation [30] and graph theory problems [31][32][33][34]. e contributions of this work are as follows: (1) we propose a novel multi-source search strategy named PS by modifying the grown rule of the Physarum foraging model in [28]; and (2) an extension algorithm named PDS is developed, considering the decision-making of each source and obstacle avoidance.…”
Section: Introductionmentioning
confidence: 99%